Side-to-side differences in knee extensor strength and fatigue - Ahtiainen, J. P.; Peltonen, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Differential loading patterns during sports training may exacerbate strength imbalances between the lower limbs that may predispose to lower extremity injuries (Rosene et al. 2010). The aim of the present study was to compare maximal power and isometric strength tests in determination of asymmetry in knee extensors; secondly, to study whether the strength differences can be explained by muscle size or neural activity; and third, to study the effects of acute loading on knee extensors strength balance. Methods: Team sport athletes (men, n=11, women, n=4; 24 ± 2 yrs.) volunteers for the study. Subjects had no history of lower extremity injuries during the past two years. The maximal power (POW) of knee extensors was determined unilaterally by pneumatic loading device (Hur 3350, Hur Ltd., Finland). Maximal isometric torque (ISO) was measured by dynamometer. EMG activity of m.vastus lateralis (VL) was determined during the strength tests. Thickness of VL was determined by ultrasound. Strength tests were performed before and after acute loading protocol of a 10 repetition maximum set in Hur device followed by approximately 5 min circuit exercise of bench stepping, lunge squats, and vertical jumps. Results: Side-to-side knee extensor strength differences did not correlate between POW and ISO tests, and laterality were not related to EMG activity or muscle size. The loading led to decreases bilaterally in POW (-5 ± 20 %, ns.) and ISO (-19 ± 9 %, p < 0.001). Acute loading decreased difference between stronger and weaker limb from 8.7 ± 7.7 % to 0.8 ± 14.2 % (p < 0.05) in POW but similar change was not observed in ISO. The loading-induced changes in EMG activity were not associated with changes in muscle strength. Discussion: Athlete`s performance detriments (Hart et al. 2014) and risks for lower extremity injuries (Keeley et al. 2011) can be evaluated by testing of strength imbalance between the lower limbs. However, determination of side difference in knee extensor strength depends on the analyzing method. In the present study, the POW and ISO showed divergent results in 6 out of 15 subjects. Neither EMG activity during the muscle actions nor muscle size of knee extensors explained the present strength differences by side. Fatiguing loading induced decreases strength more in stronger compared to weaker limb in POW but not in ISO. Changes in symmetry of limb strength by fatigue may ultimately decrease athlete`s efficiency in sport activities. The present findings suggest that maximal power tests in fatiguing conditions could be promising diagnostic tool in determination of functional asymmetry in the lower limb strength.